Caregiving Experience in A Spouse with Schizophrenia: A Scoping Review - Annisa, Vena; Suryani, Suryani; Sriati, Aat (GLOBAL HEALTH SCIENCE GROUP, 2024)
The problem of schizophrenia will be felt by several couples in the Childbearing age. So the role of caregivers is very important for the recovery process of schizophrenia sufferers. The symptoms that appear in schizophrenia patients will affect the quality of life of the partner as caregiver. Spouse will experience various impacts physically, psychologically, socially and spiritually. This scoping aims to determine the experiences of couples of childbearing age in caring for partners with schizophrenia. This research uses a scoping review method research design. Articles were obtained based on research results through several electronic databases such as SagePub, Ebsco, Pubmed, Google Scholar and Scopus. Articles were selected from 2018 - 2023 and 10 article was found that matched the theme raised.. The results of the analysis in this scoping review illustrate that spouse of childbearing age who care for patients with schizophrenia experience subjective and objective burdens. Apart from that, patients with schizophrenia experience sexual dysfunction due to taking drugs, this can trigger a breakdown in relationships, because biological needs cannot be met. financial problems, confusion in caring for a partner and obstacles in carrying out activities are also things that many couples experience. So it can be concluded that caring for a partner with schizophrenia will cause various problems both biologically, psychologically, sexually and financially.